El Pago de la Pensión Alimenticia por los Obligados Subsidiarios - Encalada Castillo, Laura Maricela (2024)
The present research work entitled “The Payment of Alimony by Subsidiary Obligors” aims to carry out a conceptual, doctrinal, and legal analysis of the payment of alimony following literally the order of priority established for the subsidiary obligors, with the purpose to determine and propose a reform to the priority order of the subsidiary obligors, allowing to sue directly the relative of the beneficiary who has the greatest economic capacity to pay alimony. In order to achieve the objectives in a concrete way, a methodology that allowed strengthening the research was used. It focuses on the use of descriptive, deductive, inductive, analytical, comparative, maieutic and statistical methods. Apart from the use of a mixed approach based on the development of a descriptive research with a longitudinal design, it was considered the use of theoretical techniques such as documentary collection, documentary observation, survey, interview, and casuistic through which it was possible to collect pertinent information and criteria from people involved in the problem. These data were reflected in the results and led to the conclusion that it is evident that in the country there is a violation of the rights of beneficiaries because it is not possible to set alimony to the subsidiaries due to the unrestricted respect of the order established in the norm, being necessary a modification to this order of priority in order to guarantee in a full and timely manner the satisfaction of the needs of children and adolescents, considering directly the subsidiary with the greatest economic capacity to assume this obligation.